MICRO CREDIT LENDING BY COMMERCIAL BANKS UNDER PRIORITY SECTOR (WITH SPECIAL REFERENCE TO KRISHNAGIRI DISTRICTS) - K., Usha; S.M., Krishnan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro finance is playing predominant role in constructing the economy of the modern world. Micro finance concepts are used in all the countries without differences. But it is widely used in the developing countries like India, Uganda, Indonesia, Serbia, and Honduras for sustainable growth in the diversified fields. Social developments are possible only where financial independence is available to the different interest participants. This purpose is fulfilled by the micro fiancé. It focuses mainly on priority sectors such as agriculture, education, small business, export credit, housing finance. This study is focusing on micro finance lending by commercial banks towards priority sectors. This study is exploratory in nature, both primary and secondary data is used. For the purpose of analysis percentage analysis, factor analysis and multiple regression analysis have been used. The Study shows that the customers are having more awareness on the Micro finance credit. But to develop and bring suitable growth suggestions have been Provide. Such as introducing diversified business strategy, filed visit, meeting the stake holders directly, and providing financial counseling to the middle class and lower and upper middle class. These strategies will lead to the financial developments.